PENGARUH TERAS BANGKU DALAM MENGURANGI EROSI TANAH PADA LAHAN PERTANIAN DI DESA PONOMPIAAN KABUPATEN BOLAANG MONGONDOW - R. Anau; D. Rumambi; L. Kalesaran (COCOS, 2023)
ABSTRACT The purpose of this study was to calculate the amount of erosion on land using bench terraces compared to land without using bench terraces and also to examine the effect of bench terraces in reducing erosion on agricultural land in Ponompiaan Vilagge, Bolaang Mongondow Regency. The method in this study is an experimental study in open land which was deliberately chosen because it has a certain slope in accordance with the research abjectives. And the data is presented in the form of tables and graphs and then analyzed descriptively. Based on the data obtained that soil and water conservation techniques in this case the use of bench terraces are very effective in preventing erosion in sloping land, data collection in this study was carried out for 51 days with 16 observations, daily rainfall data taken from the nearest station quite consistent with monthly rainfall data for 2021 from the BMKG of North Sulawesi. This study did not measure the intensity of rainfall. The data shows that the amount of rainfall and the duration of the occurrence of rain affect the sediment collected on land using bench terraces and non-terrace land (control). Judging from the existing data, the amount of sediment on the experimental land using the bench terraces was 56.69 kg, while the sediment on the non-core (control) was 163.3 kg. Data from land using bench terraces and non-terrace land (control) showed that the difference in sediment was 65.6 % greater than the sediment collected on nonterrace land (control). Keywords : Erosion, Bench Terrace, Conservation